2020
DOI: 10.1186/s43166-020-00010-9
|View full text |Cite
|
Sign up to set email alerts
|

Significance of serum albumin and derived neutrophil-to-lymphocyte ratio score in assessment of disease activity in rheumatoid arthritis patients

Abstract: Background: Albumin and derived neutrophil to lymphocyte ratio (dNLR) are known biomarkers that can reflect systemic inflammation and it has been hypothesized that combination of both markers in one score (albumin-dNLR score) can be useful in monitoring rheumatoid arthritis (RA) patients. The current study intended to measure albumin-dNLR score in patients with RA in the order to find whether these new biomarkers could reflect the activity of the disease and the articular activity detected by ultrasonography. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Decreased serum ALB levels have been extensively described in rheumatoid arthritis (RA), mainly due to suppression of hepatic production by inflammatory cytokines storm, hemodilution and malnutrition status [ 89 ].…”
Section: Albumin In Rheumatologic Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased serum ALB levels have been extensively described in rheumatoid arthritis (RA), mainly due to suppression of hepatic production by inflammatory cytokines storm, hemodilution and malnutrition status [ 89 ].…”
Section: Albumin In Rheumatologic Autoimmune Diseasesmentioning
confidence: 99%
“…Ganeb S et al (2020) observed that serum ALB levels are significantly lower in RA subjects (median 3.9; 3.5–4.35; p < 0.001) than in healthy controls; moreover, when stratifying RA patients by disease activity, as assessed by Disease Activity Score-28 (DAS28), serum ALB was significantly decreased in patients with high disease activity compared with both those in moderate activity and those in remission [ 89 ].…”
Section: Albumin In Rheumatologic Autoimmune Diseasesmentioning
confidence: 99%
“…In our study, serum albumin was marginally lower in our RA patients, with a median of 3.9 (3.5 -5) mg/dl versus 4.4 (3.5-5.5) mg/dl in the controls. Ganeb et al (24) discovered a similar result, with RA patients having reduced blood albumin levels median of 3.9 (3.5-4.35) mg/dl) than controls. Patients with RA have a lower albumin level, as demonstrated by the work of Zhang et al (25) , Ben-Hadj-Mohamed et al (26) , and Tsuji et al (27) since albumin targets inflamed joints, active RA patients commonly develop hypoalbuminemia (6) .…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, albumin, being the most abundant protein in the synovial fluid, plays a key role in joint lubrication and the transportation of small molecules in different tissues of the joint [83,84]. Changes in albumin concentrations in the synovial fluid are often associated with inflammatory conditions such as OA or rheumatoid arthritis, with levels typically decreasing, rendering it a potential biomarker in clinical settings [85,86]. The incomplete and controversial information regarding the effect of albumin on chondrogenesis and joint homeostasis needs further investigation into its natural role and variations in healthy and pathologic joints as well as how it may be a potential therapeutic agent.…”
Section: Discussionmentioning
confidence: 99%